INTRODUCING BAKER BOOK HOUSE - Lategan, Bernard C. (Scriptura, 1981)
From time to time this section will be devoted not to biblical literature as such, but to the publishers behind the scenes who produce this material. By doing so we hope to introduce our readers to publishing trends and traditions and to contribute to a more informed use of the rich resources available in this field. Our aim shall be to present a balanced selection from the whole spectrum of publishers in this area, ranging from those working in a more conservative traditions to those representing a more critical approach.The decision to start off with Baker Book House was motivated by two reasons. Firstly, publications of this firm have increasingly gained prominence and secondly, the history of Baker Book House reveals close parallels to the role played by reformed publishing in this country.